2007
DOI: 10.1021/bc700161p
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Bifunctional Chelate for Radiolabeling Humanized Anti-CEA Antibody with In-111 and Cu-64 at Either Thiol or Amino Groups: PET Imaging Of CEA-Positive Tumors with Whole Antibodies

Abstract: Radiolabeled anti-carcinoembryonic antigen (CEA) antibodies have the potential to give excellent images of a wide variety of human tumors, including tumors of the colon, breast, lung, and medullar thyroid. In order to realize the goals of routine and repetitive clinical imaging with anti-CEA antibodies, it is necessary that the antibodies have high affinity for CEA, low cross reactivity and uptake in normal tissues, and low immunogenicity. The humanized anti-CEA antibody hT84.66-M5A (M5A) fulfills these criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 21 publications
1
61
2
Order By: Relevance
“…The uptake in C15A.3 lesions was lower than in subcutaneous LS-174T tumors as reported by Li et al [11]. The differences in the cell type and tumor location could both contribute to a different tumor microenvironment, explaining the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The uptake in C15A.3 lesions was lower than in subcutaneous LS-174T tumors as reported by Li et al [11]. The differences in the cell type and tumor location could both contribute to a different tumor microenvironment, explaining the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 47%
“…It has been previously reported that the M5A antibody shows outstanding binding characteristics in subcutaneous CEA tumor models [11]. Therefore, we decided to use this promising antibody in a more challenging and novel model of syngeneic liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in studies with 64 Cu-labeled anti-CEA mAbs that TACs obtained with microPET and this calibration method produce good agreement with TACs measured for tumor, liver, and blood in separate, parallel groups of mice by direct tissue assay. 24 Of the two anticipated problems for 124 I, high ␤ ϩ energy, and true-coincidence ␥-ray background, the former appears to be the more significant. The positron-range effect can be modeled in iterative reconstruction, and some work has been done on this for MAP.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Li et al, 26 a humanized anti-CEA intact antibody, hT84.66-M5A (M5A), was labeled with 64 Cu using the chelator 1,4,7-tris(carboxymethyl)-10-(vinylsulfone)-1,4,7,10-tetraazacy clododecane (DO3A-VS). The 64 Cu-labeled conjugate (NH-DO3A-VS-M5A or SH-DO3A-VS-M5A) was then injected into mice bearing CEA-expressing LS-174T tumors.…”
Section: A 64mentioning
confidence: 99%